2014
DOI: 10.3382/ps.2013-03807
|View full text |Cite
|
Sign up to set email alerts
|

Expression of digestive enzymes and nutrient transporters in Eimeria acervulina-challenged layers and broilers

Abstract: Avian coccidiosis is a disease caused by intestinal protozoa in the genus Eimeria. Clinical signs of coccidiosis include intestinal lesions and reduced feed efficiency and BW gain. This growth reduction may be due to changes in expression of digestive enzymes and nutrient transporters in the intestine. The objective of this study was to examine the differential expression of digestive enzymes, transporters of amino acids, peptides, sugars, and minerals, and an antimicrobial peptide in the small intestine of Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 31 publications
8
67
0
Order By: Relevance
“…Images were captured using 100x magnification. studies, LEAP2 was down-regulated in all 3 segments of the small intestine (Su et al, 2014(Su et al, , 2015. In this study, ceca were not collected.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Images were captured using 100x magnification. studies, LEAP2 was down-regulated in all 3 segments of the small intestine (Su et al, 2014(Su et al, , 2015. In this study, ceca were not collected.…”
Section: Discussionmentioning
confidence: 80%
“…The antimicrobial peptide LEAP2 was down-regulated in the small intestine following challenge with E. acervulina, E. maxima, E. tenella, and E. praecox (Casterlow et al, 2011;Sumners et al, 2011;Paris and Wong, 2013;Su et al, 2014Su et al, , 2015Yin et al, 2015). Using a necrotic enteritis model induced by initial challenge with E. maxima followed by challenge with Clostridium perfringens, Hong et al (2012) reported the expression of HDP in the jejunum of both Cobb and Ross broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real time PCR was performed on an Applied Biosystems 7300 system with SYBR green using the following conditions for all genes: 50°C for 2 min and 95°C for 10 min followed by 40 cycles of 95°C for 15 s and 60°C for 1 min. Samples were run in duplicate and relative gene expression data were analyzed using the 2 −ΔΔCt method (Livak and Schmittgen, 2011) as described in Su et al (2014). β-actin was chosen as the reference gene, because the Ct value for β-actin was the same for control and infected samples.…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Liver-expressed antimicrobial peptide-2 (LEAP2) is an antimicrobial peptide that is part of the innate immune system (Lynn et al, 2004). Recent studies have revealed a downregulation of LEAP2 in chickens infected with E. maxima, E. praecox and E. acervulina (Casterlow et al, 2011;Fetterer et al, 2014;Paris and Wong, 2013;Su et al, 2014;Sumners et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation